Experimental analysis of racing car chassis for Modal Identification / M. N. Aizat Zainal ...[et al.] - Aizat Zainal, M. N.; Anuar, M. Azhan; Mat Isa, A.A; Adenan, M. Shahriman (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Racing car chassis is a complex structure fabricated to suit highly demanding racing specifications. Its vibration modes range from a very low to high frequencies and need to be determined in order to ensure optimum performance. The purpose of this study is to determine modal parameters (e.g., natural frequencies and mode shapes) of a racing car chassis using Operational Modal Analysis (OMA). OMA is an experimental technique that applies random excitation while measuring only output response. Initially, the natural frequencies and mode shapes of chassis structure are determined from non-parametric OMA technique which is Frequency Domain Decomposition (FDD). Frequency Response Function (FRF) plots are then obtained from Experimental Modal Analysis (EMA) technique. Results from both FDD and EMA are validated and compared to ensure that FDD result can be further used in OMA methods of analysis. Only two out of four identification algorithms in parametric OMA techniques will be applied, namely Enhanced Frequency Domain Decomposition (EFDD) and Canonical Variant Analysis of Covariance-driven Stochastic Subspace Identification (SSI-CVA) methods. Finally, the natural frequencies and mode shapes obtained from each OMA techniques will be compared, discussed and concluded. The results from this study can be utilized to avoid resonance on chassis structures that will affect the performance of the racing car’s structure significantly.